2018
DOI: 10.1007/s40618-018-0839-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity and secretion and adipokine profile in patients with Cushing’s disease treated with pasireotide

Abstract: 12 months of treatment with pasireotide in CD is associated with an impairment of insulin secretion and an improvement of adipose function without any interference in insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 46 publications
2
15
3
Order By: Relevance
“…Pasireotide‐induced insulin suppression led to hyperglycemia, which was attenuated by GLP‐1RA, although not by a DPP4 inhibitor. Pasireotide ameliorated hypercortisolemia through the stimulation of SSTR5, thereby, suppressing the secretion of ACTH 1,2,4 . However, pasireotide also suppressed the secretion of insulin 3‐5,9 directly via SSTR5 in pancreatic β cells and indirectly by suppressing GIP and GLP1 3,5,9 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Pasireotide‐induced insulin suppression led to hyperglycemia, which was attenuated by GLP‐1RA, although not by a DPP4 inhibitor. Pasireotide ameliorated hypercortisolemia through the stimulation of SSTR5, thereby, suppressing the secretion of ACTH 1,2,4 . However, pasireotide also suppressed the secretion of insulin 3‐5,9 directly via SSTR5 in pancreatic β cells and indirectly by suppressing GIP and GLP1 3,5,9 .…”
Section: Discussionmentioning
confidence: 98%
“…The broad stimulation of somatostatin receptor subtypes, including somatostatin receptor type‐5 (SSTR5), suppresses adrenocorticotropic hormone (ACTH) levels, along with hypercortisolemia, and reduces tumor volume 2 . However, SSTR5 stimulation also suppresses insulin secretion from pancreatic β‐cells, leading to hyperglycemia 3‐5 . Owing to this inevitable adverse event, physicians hesitate to prescribe the beneficial drugs to relevant patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CD patients, the pituitary-directed agents pasireotide and cabergoline may also be evaluated as treatment options for hypercortisolism control during a COVID-19 pandemic, although their intermediate efficacy, with hormonal control reached in 25% and 31% of treated patients, respectively [ 67 ], should limit their use as second-line approaches except for patients with mild CS [ 28 , 83 ]. In particular, pasireotide should not be preferred, due to hyperglycaemia-related adverse events, which may occur in up to 73% of treated patients [ 67 , 84 86 ], and to the higher morbidity and mortality in COVID-19 patients with diabetes mellitus [ 2 ].…”
Section: Therapeutic Approach To Patients With Active Cushing’s Syndrmentioning
confidence: 99%
“…HOMA-β calculations and fasting insulin levels in a small study demonstrated insulin secretion decreased by nearly 50% after 12 months’ pasireotide usage in patients with CD ( p = 0.015; p = 0.007, respectively). However, euglycemic hyperinsulinemic clamp evaluation did not demonstrate differences in insulin sensitivity before or after initiation of pasireotide ( 39 ). Glucagon levels were also decreased on therapy, but to a lesser extent ( 40 ).…”
Section: Adverse Eventsmentioning
confidence: 99%